Research on the Mechanism of HRP Relieving IPEC-J2 Cells Immunological Stress Based on Transcriptome Sequencing Analysis - Li, Muyang; Chen, Lu; Zhao, Yiran; Sun, Hui; Zhao, Lei (Frontiers in Nutrition, 2022)
Early weaning increased the economic benefits of piglets. However, early weaning damages the intestinal barrier of piglets and causes immunological stress. The mechanism by which Hippophae rhamnoides polysaccharide (HRP) alleviates lipopolysaccharide (LPS)-induced intestinal porcine epithelial cells (IPEC-J2) inflammatory damage was investigated using proteomics in our previous studies. In this study we employed RNA-sequencing (RNA-seq) to determine the level and function of differentially expressed genes (DEGs) and further explore the mechanism of the HRP anti-inflammatory and immune process. The differential expression analysis indicated that 3622, 1216, and 2100 DEGs in the IPEC-J2 cells were identiﬁed in C vs. L, L vs. H6-L, and C vs. H6-L, respectively. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis foundsix identified pathways related to the immune system. Additionally, we used the Science, Technology, Engineering, and Math (STEM) program to categorize the 3134 DEGs that were differentially expressed in H2-L, H4-L and H6-L into eight possible expression profiles, in which 612 were clustered into two profiles. The accuracy and consistency of RNA-seq data were validated by the results of qRT-PCR of the nuclear factor of kappa light polypeptide gene enhancer in B-cells 2 (NFKB2), MAP kinase interacting serine/threonine kinase 2 (MKNK2), mitogen-activated protein kinase kinase 1 (MAP2K1), mitogen-activated protein kinase kinase kinase 8 (MAP3K8), Ras-related protein R-Ras (RRAS), TNF receptor-associated factor 1 (TRAF1), NF-kappa-B inhibitor alpha (NFKBIA), interleukin 8 (IL8), tumor necrosis factor, alpha-induced protein 3 (TNFAIP3), and transforming growth factor beta-1 (TGFB1). Transcriptome sequencing also indicated that HRP reduced the expression levels of related DEGs and inhibited the activation of the mitogen-activated protein kinase (MAPK)/nuclear factor kappa-B (NF-κB) signaling pathway. Our findings indicate that the application of HRP in piglet diets during the early weaning period can improve intestinal epithelial function and integrity, and relieve intestinal damage, and improve piglet health.